SIFAT ORGANOLEPTIK SNACK BAR TEPUNG SUKUN KACANG MERAH PENDERITA DIABETES MELITUS TIPE II - Wina Nabila Turohim; Fred Agung Suprihartono; Gurid Mulyo; Ramanda Alfika; Hervina Sahrul Nasution; Enung Nurhotimah (Poltekkes Kemenkes Bandung, 2026)
Background: Diabetes mellitus type II is a chronic metabolic disease that requires dietary management, including low glycemic index and high-fiber snacks to help control blood glucose levels. Objective: This study aimed to determine the organoleptic properties of a snack bar made from breadfruit flour and red bean flour with dried apple topping as a snack for type II diabetes mellitus patients. Methods: This experimental study used three formulations: F1 (20%:80%), F2 (40%:60%), and F3 (10%:90%) breadfruit to red bean flour ratios. Hedonic testing was conducted by 30 semi-trained panelists using a 1-7 scale. Nutritional content was calculated using the Indonesian Food Composition Table (TKPI) 2019 and USDA data, and the estimated glycemic index was calculated using the overall glycemic index formula. Results: Formula F3 (10%:90%) had the highest overall acceptance (mean score 5.67) and was most preferred for taste, aroma, and texture. Nutritional content per serving of F3 was 165 kcal energy, 8.2 g protein, 5.3 g fat, 22.3 g carbohydrate, and 5.9 g fiber. The estimated glycemic index of all three formulas was low (<55). Conclusion: The snack bar with 10% breadfruit and 90% red bean flour was the most acceptable, had low glycemic index and high fiber, and was suitable as a snack for type II diabetes mellitus patients.